The reactivity of diazabutadienes towards low oxidation state group 13 iodides and the synthesis of a new gallium(I) carbene analogue - BAKER, ROBERT (My University, 2002)
The reactions of two diazabutadiene ligands, Ar-DAB [(ArN[double bond, length as m-dash]CH)2 , Ar = 2,6-Pri2C6H3] and But-DAB [(ButN[double bond, length as m-dash]CH)2] with either GaI or an AlI3/Al mixture have afforded the paramagnetic compounds, [{IGaII(But-DAB)}2], [I2GaIII(But-DAB)] and [I2AlIII(Ar-DAB)] which have been characterised by X-ray crystallography and EPR spectroscopy. In addition, the diamagnetic, ionic complex, [I2AlIII(Ar-DAB)]I, has been prepared and structurally characterised. The reduction of [I2GaIII(Ar-DAB)] with potassium metal in the presence of various Lewis bases has led to three structurally characterised compounds, [{(Et2O)KGaI(Ar-DAB)}2], [{(TMEDA)KGaI(Ar-DAB)}2] and [:GaI(Ar-DAB)]2[{K(18-crown-6)}2(μ-18-crown-6)], which contain the second example of an anionic gallium(I) carbene analogue. In addition, the former two compounds display GaGa interactions in the solid state which are unprecedented for this complex type.
PUBLISHED
Keywords: Chemistry